Effect of dimethylamine on the gas phase sulfuric acid concentration measured by Chemical Ionization Mass Spectrometry. Issue 6 (24th March 2016) - Rondo, L.; Ehrhart, S.; Kürten, A.; Adamov, A.; Bianchi, F.; Breitenlechner, M.; Duplissy, J.; Franchin, A.; Dommen, J.; Donahue, N. M.; Dunne, E. M.; Flagan, R. C.; et al.
Abstract: Sulfuric acid is widely recognized as a very important substance driving atmospheric aerosol nucleation. Based on quantum chemical calculations it has been suggested that the quantitative detection of gas phase sulfuric acid (H2 SO4 ) by use of Chemical Ionization Mass Spectrometry (CIMS) could be biased in the presence of gas phase amines such as dimethylamine (DMA). An experiment (CLOUD7 campaign) was set up at the CLOUD (Cosmics Leaving OUtdoor Droplets) chamber to investigate the quantitative detection of H2 SO4 in the presence of dimethylamine by CIMS at atmospherically relevant concentrations. For the first time in the CLOUD experiment, the monomer sulfuric acid concentration was measured by a CIMS and by two CI‐APi‐TOF (Chemical Ionization‐Atmospheric Pressure interface‐Time Of Flight) mass spectrometers. In addition, neutral sulfuric acid clusters were measured with the CI‐APi‐TOFs. The CLOUD7 measurements show that in the presence of dimethylamine (<5 to 70 pptv) the sulfuric acid monomer measured by the CIMS represents only a fraction of the total H2 SO4, contained in the monomer and the clusters that is available for particle growth. Although it was found that the addition of dimethylamine dramatically changes the H2 SO4 cluster distribution compared to binary (H2 SO4 ‐H2 O) conditions, the CIMS detection efficiency does not seem to depend substantially on whether an individual H2 SO4 monomer is clustered with a DMA molecule. The experimental observations are supported by numerical simulations based on A Self‐contained Atmospheric chemistry coDe coupled with a molecular process model (Sulfuric Acid Water NUCleation) operated in the kinetic limit. Key Points: H2 SO4 concentration measured by CIMS in CLOUD was influenced by the presence of dimethylamine CIMS's detection efficiency is not substantially influenced by the presence of dimethylamine Information of sulfuric acid cluster composition by CI‐APi‐TOF explains most of the observed effect